Comparative Study of the Antifungal Effectiveness of Massoia Essential Oil-Based SMMDF Formulations with HPMC and PVP Polymers against Candida albicans - Devilke Yandriyani; Eva Monica (Universitas Ngudi Waluyo, 2025)
Oral diseases, like oral candidiasis caused by Candida albicans, remain a common and troubling health issue in Indonesia. Massoia essential oil (Massoia aromatica Becc.), which contains C-10 massoialactone, has proven antifungal properties. However, its limited solubility affects how well it is absorbed into the body. This study aimed to evaluate the antifungal effectiveness of Self-Micro-emulsifying Mouth Dissolving Film (SMMDF) formulations that incorporate massoia essential oil, using either HPMC or PVP polymers, against C. albicans in a laboratory setting. The test fungus was cultured on PDA and prepared into a suspension standardized to 0.5 McFarland, followed by antifungal testing using the well diffusion method on PDA medium. Nystatin served as the positive control, while formulations without massoia essential oil served as the negative control. The results showed that the average inhibition zones for SMMDF with HPMC and PVP polymers were 10.85 mm and 11.51 mm, respectively—both considered strong and larger than the positive control (6.68 mm). An independent sample t-test showed no significant difference between the two polymers (p = 0.735), suggesting that the antifungal activity mainly stemmed from the massoia essential oil itself. These results suggest that massoia essential oil-based SMMDF holds significant potential as an effective antifungal solution against C. albicans, with no major difference in effectiveness between HPMC and PVP as the polymers used to form the film.